Implementation of embedded generation in distribution system using Evolutionary Programming (EP) - Wan Noorhana Wan Nordin (School of Electrical Systems Engineering, 2009)
Recent years, the number of embedded generators installed in distribution system has been increasing in many parts of the world. Depending on their operating characteristics and locations, embedded generators could significantly affect the voltage profile, network losses, and fault level in the distribution system. This thesis studied on the implementation of minimization the power losses of embedded generation in a distribution system. The calculation method used in this thesis is the Newton-Raphson method, and the software that had been used to compile the program is the MATLAB software. In order to determine the optimal output of the embedded generators, an evolutionary programming optimization technique was developed with an objective to minimize the distribution losses while satisfying the voltage constraint in the system. The proposed technique was tested on the 6 bus distribution system and the results shown a significant reduction in distribution losses and voltage profile improvement of the embedded generation at the suitable location and optimal sizing.